2016
DOI: 10.1038/srep25325
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi for Chronic Pain Conditions: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Several studies reported that Tai Chi showed potential effects for chronic pain, but its role remains controversial. This review assessed the evidence regarding the effects of Tai Chi for chronic pain conditions. 18 randomized controlled trials were included in our review. The aggregated results have indicated that Tai Chi showed positive evidence on immediate relief of chronic pain from osteoarthritis (standardized mean difference [SMD], −0.54; 95% confidence intervals [CI], −0.77 to −0.30; P < 0.05). The val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 36 publications
3
72
0
3
Order By: Relevance
“…43 A more recent meta-analysis, however, found that long-term use of Tai Chi (12-20 weeks) appears to be more effective than short-term Tai Chi (6-10 weeks) in improving chronic OA pain. 44 Tai Chi has also shown small positive effects on overall physical health and satisfaction with general health in patients with OA. 41 The recent ACP guidelines support the use of Tai Chi as first-line treatment for chronic LBP, 2 and the 2012 ACR guidelines conditionally recommend Tai Chi for patients with OA of the knee.…”
Section: Exercise Therapymentioning
confidence: 99%
“…43 A more recent meta-analysis, however, found that long-term use of Tai Chi (12-20 weeks) appears to be more effective than short-term Tai Chi (6-10 weeks) in improving chronic OA pain. 44 Tai Chi has also shown small positive effects on overall physical health and satisfaction with general health in patients with OA. 41 The recent ACP guidelines support the use of Tai Chi as first-line treatment for chronic LBP, 2 and the 2012 ACR guidelines conditionally recommend Tai Chi for patients with OA of the knee.…”
Section: Exercise Therapymentioning
confidence: 99%
“…Many different types of Tai Chi exist, but most consist of movement, meditation and breathing, while concentrating on the mind and maintaining low intensity [19, 20], and further modulate various aspects of the body including the physical, the psychological, mood and spirit [21]. In the theory of Chinese medicine (CM), Tai Chi can maintain the harmony between qi and the blood , keep yin and yang in balance and also enhance immunity [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…yWoo, J., indicaron que los adultos mayores con el tai chi mejoran su componente físico de la calidad de vida relacionada con la salud, concluyendo que la práctica del tai chi es beneficiosa para los ancianos en las residencias (15). Además, Kong, L. J. et al, en su estudio concluye que existe evidencia positiva con respecto a los efectos del tai chi sobre el dolor de la osteoartritis crónica, el dolor lumbar y la osteoporosis (18).…”
Section: Disminuyendo Dolencias Corporalesunclassified